An Analysis Directive Speech Acts of Main Character In The Cruella Movie - gisela triseptia nabila; tri budiarta (LIAISON JOURNAL OF BEST, 2022)
Directive speech act is utterance of the speaker to get the hearer to do something. Theobjectives of the research is to identify and analyze directive speech acts using the theory proposed by John R Searle and the functions of directive speech acts using the theory proposed by Janet Holmes. The data of this research were all utterances directive speech act spoken by the main character. The method used in this research was descriptive qualitative and used documentation technique as a data collection method. The result showed that the researcher found 60 data of type directive speech acts in the Cruella movie which are divided into: asking (27), commanding (11), inviting (2), forbidding (6), requesting (10) and suggesting (5). The researcher found 33 data functions of directive speech found in the film they are: Directive (24) and referential (9). From the results of the research, it is known that Asking is the most types. For functions directive speech acts, the most found is directive.Key words: Directive Speech Acts, Language Function, Movie.